Related muscular adaptations to corporal regions that actively participate in the flight of Anhima cornuta (Aves: Anseriformes, Anhimidae) - Manzanares, Marcos Antonio (2007)
The form and correspondence between the muscular and bony anatomy shows, principally, the locomotive habit of the birds. The screamers are a peculiar group in the Aves Class, because their bony adaptations (and therefore, muscular adaptations), the absence of uncinate processes, two long and sharp metacarpal spurs, their bones are far more pneumatic than in others birds and the bony foramens development. Four specimens of Anhima cornutaand four specimens of linked species (two of Dendrocygna bicolorand two of Dendrocygna viduata) were studied and compared, and their muscular components of the spine, trunk, forelimbs, hind limbs, tail and waists were analyzed, anatomically and quantitatively (origin and insertion surface, long, mass). The study revealed that Anhimahas a great development of the intercostals and intervertebrals muscles (thoracic and lumbar regions), evidencing an adaptation to the absence of uncinate processes. Anhimahas muscular fascicles, proportionally less heavy and smaller that Dendrocygna, indicating a less capacity of the flight. Some metacarpal tendons and muscular fibers whose inserts in the first digit in Dendrocygna, in Anhima are inserted in the spurs base, showing the few flight control. The hind limbs musculature in Anhimais much more developed, in size and proportional mass, evidencing a great activity in this area, specifically in the flight propulsion and in terrestrial habits.